THE VARIATION OF MICROSTRUCTURE FOR THE TL2BA2CA2CU3O10-DELTA PHASE WITH T(C) OF 119 AND 127-K - Liu, R; Hervieu, M; Michel, C; Raveau, B; Edwards, P (1992)
We report the synthesis, superconducting properties, X-ray diffraction, and microstructure of the Tl2Ba2Ca2Cu3O10-δ phase having Tc of 119 K (an as-synthesized sample) and 127 K (a vacuum-annealed sample). The electron diffraction and [010] bright field image of the 119-K phase indicate a nearly perfect periodicity along the c-axis of Tl2Ba2Ca2Cu3O10-δ. In contrast, the 127-K phase exhibits a significant change in microstructure, where intergrowth defects of Tl2Ba2Cu3Cu4O12-δ and Tl2Ba2Ca2Cu3O9-δ are observed for this vacuum-annealed sample. These kinds of intergrowth defects arising from the unavoidable loss of thallium during the high-temperature (750°C), extended vacuum annealing (10 days) and the resulting oxygen nonstoichiometry appear to play an important role in the enhancement of Tc from 119 to 127 K. © 1992.